Pomiar kapitału ludzkiego w organizacji - Wyrzykowska, Barbara (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2008)
The 21st century is the time of effective human capital management. In the traditional approach the enterprise’s value is influenced by amount of material assets and their ability to generate future profits estimated in cash flows. Most of the companies however build their economical power but basing only on book value is very limited. This suggests that there are assets visible to the market, but not reflected in the financial reports. In the assessment of companies’ running effectiveness and their market value there are several issues that become more and more important: knowledge, management’s and employees’ skills, innovations in company’s running, flexibility of management, promptness and quality of decision making. It seems that in the future swift and successful companies will make use the human capital reporting, what will give them competitive advantage at the valuation